Acceptance of takaful among non-muslim in Kota Bharu / Muhammad Hilmi Sukery - Sukery, Muhammad Hilmi (2013)
Takaful is derived from the Arabic word kafalah, which is a pact that guaranties individuals in a group against loss or damage sustained by anyone of them (Jacky Lim, 2010). In easy word is Islamic compliance insurance. This research is focusing on the acceptance of takaful among non-Muslim in Kota Bharu. The acceptance will be identified based on three variables; attitude and perception, information, and takaful provider and agent’s behaviour. For this purpose, the researcher used primary data, which is a structured questionnaire that been distributed among non-Muslim community around Kota Bharu. Data that been gathered in these sets of questionnaire will be analyzed by using SPSS 20 to find the descriptive statistics and regression analysis such as multiple regression model and Durbin Watson statistics